Rare bird documentation form for Lesser Black-backed Gull at Lindsay Park Harbor in 1995 - Petersen, Peter C.et al (1995)
Rare bird documentation form for a Lesser Black-backed Gull at Lindsay Park Harbor in Scott County, IA on February 3 and 16, 1995. Epson - sheet feed